2020
DOI: 10.1111/ped.14257
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Buzzy® on pain and anxiety during catheterization in children

Abstract: Background: The use of a peripheral intravenous cannula is a common clinical practice, and it is known to be a major source of pain and anxiety in children. The aim of this study was to examine the effect of the use of the Buzzy â on pain and anxiety in children during peripheral cannula application. Methods: The research sample consisted of 60 children between the ages of 8 and 16. For children in the experimental group, external cold and vibration were applied by means of the Buzzy â device. Before and durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 24 publications
0
2
0
1
Order By: Relevance
“…Los estudios mencionados difieren de los resultados obtenidos por Yilmaz et al, quienes incluyeron 60 niños de entre 8 y 16 años, pues no encontraron diferencia estadísticamente significativa entre la intensidad del dolor posterior a cateterización venosa peri-férica con el uso del dispositivo Buzzy® entre el grupo experimental y el grupo control 41 .…”
Section: Buzzy® Realidad Virtual Y Técnicas Tradicionalesunclassified
“…Los estudios mencionados difieren de los resultados obtenidos por Yilmaz et al, quienes incluyeron 60 niños de entre 8 y 16 años, pues no encontraron diferencia estadísticamente significativa entre la intensidad del dolor posterior a cateterización venosa peri-férica con el uso del dispositivo Buzzy® entre el grupo experimental y el grupo control 41 .…”
Section: Buzzy® Realidad Virtual Y Técnicas Tradicionalesunclassified
“…The average pain score in the music group was 5.50±1.55, the Hugo point acupressure was 5.50±1.57 and the control was 7.57±1. 45 3…”
Section: Semiexperimental Studymentioning
confidence: 99%
“…In a recently published study, Buzzy® was shown to be less effective than lidocaine patches, and most of the children wanted to remove the freezable wings before the end of the procedure because they started to feel uncomfortable with the cold 43 . Other studies showed that Buzzy® was not effective in reducing pain in peripheral venous access puncture 44,45 .…”
Section: Semiexperimental Studymentioning
confidence: 99%